Deiksis dalam Film Habibie dan Ainun (2012) serta Relevansinya terhadap Pendidikan Karakter - Elyna Rafiza Zaliana; Naura Lutfia Fajriani; Angela Merici Tamara Wibowo; Farah Maulida Ayu Zahara; Salma Ayu Aini Zulfa; Asep Purwo Yudi Utomo; Ngabiyanto Ngabiyanto (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to examine the use of deixis in the film Habibie and Ainun (2012) through a pragmatic approach and to explore its implications for character education. The research employs a descriptive qualitative method by analyzing utterances containing personal, spatial, temporal, discourse, and social deixis in the main characters’ dialogues. The data were obtained through transcription and contextual interpretation to uncover the pragmatic meanings embedded in the linguistic expressions. The findings reveal that deixis functions not only as a linguistic reference marker but also as a medium for expressing and reinforcing character values such as loyalty, responsibility, perseverance, and love. The contextual use of language in the film reflects the process of moral formation and emotional depth, demonstrating how language contributes to shaping character development. This study contributes to the development of Indonesian language learning by emphasizing the integration of pragmatic analysis and character education through film media. Therefore, it is recommended that language educators utilize educational films containing pragmatic elements as effective learning resources to enhance both linguistic competence and moral awareness among students.